Dari Kepuasan hingga Loyalitas: Menjelajahi Bagaimana Kualitas Layanan, Harga Wajar, dan Suasana Toko Mempengaruhi Belanja Pelanggan - Wenti Ayu Sunarjo; Siti Nurhayati; Titi Rahayu Prasetiani; Amalia Ilmiani; Choliq Sabana; Vu Hung Dang; Laela Nur Fahmi (Jurnal Akuntansi, Manajemen dan Ekonomi, 2026)
This study investigates the influence of service quality, price fairness, and store atmosphere on customer loyalty through the mediating role of customer satisfaction, using Indomaret customers in Pekalongan City as the research context. Employing a quantitative research design with 120 respondents selected through purposive sampling, data were collected via structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling. The result in this study are (1) service quality have a positive insignificant effect on customer satisfaction, (2) price fairness have a positive insignificant effect on customer satisfaction, (3) store atmosphere have a positive insignificant effect on customer satisfaction, (4) service quality have a positive insignificant effect on customer loyalty, (5) price fairness have a positive insignificant effect on customer loyalty, (6) store atmosphere have a positive insignificant effect on customer loyalty, (7) customer satisfaction have a positive insignificant effect on customer loyalty, (8) customer satisfaction is able to mediate the relationship service quality on customer loyalty, (9) price fairness is able to mediate the relationship service quality on customer loyalty, (10) store atmosphere is able to mediate the relationship service quality on customer loyalty. These findings indicate that high-quality service, fair pricing, and a pleasant store environment are essential in creating satisfied and loyal customers in the retail industry. The study contributes to understanding consumer behavior in the modern retail sector and offers managerial implications for retail operators to strengthen customer relationships through continuous improvement in service delivery, pricing transparency, and store ambiance.